PENGARUH KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP KINERJA KARYAWAN BUMN ( Studi Kasus PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Teluk Kuantan) - Larbiel Hadi (JURNAL AL-IQTISHAD, 2014)
This study aims  to determine the effect of financial compensation to the performance of employees of PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Teluk Kuantan, the influence of non-financial compensation to the performance of employees of PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Teluk Kuantan, the influence of financial and nonfinancial compensation simultaneously to the performance of employees of PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Teluk Kuantan and whether the performance difference between regular employees and contract employees of PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Teluk Kuantan. The sample in this study amounted to 44 respondents were distributed to the employees of PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Teluk Kuantan. Data analysis methods used are quantitative analyzes using the validity test, reliability test, test for normality, the assumption of classical test, multiple linear regression analysis and mean difference test. The results of studies using multiple linear regression analysis is financial compensation and a significant positive effect on the performance of employees of PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Teluk Kuantan, non financial compensation and a significant positive effect on the performance  of employees of PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Teluk Kuantan, financial and nonfinancial compensation simultaneously positive and significant effect on the performance of employees of PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Teluk Kuantan, while the test results by using the average difference is there is no performance difference between regular employees and contract employees of PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Teluk Kuantan.